Personal Recovery from Serious Mental Illness - Thongsalab, Jutharat (Babali Publisher, 2020)
Personal rehabilitation from severe mental illness (SMI) refers to the cycle of living independent and active lives in the community, where individuals with significant mental disorders can be satisfactory. The aim of the concept analysis to clarify what is meant by a personal recovery of SMI internationally by the attributes, antecedents, and consequences. This study using a technique the analysis method of Walker & Avant through 8 steps techniques. The attributes of personal recovery of SMI include connectedness, hope and optimism about future, identity, meaning in life, and empowerment. Antecedents of personal recovery of SMI is a stigma attached to a mental health diagnosis. The consequences of personal recovery of SMI are usual from SMI, self-restoration, and excellent Quality of life. Symptom reduction (e.g., clinical recovery) becomes an integral part of someone's recovery if the person is something they want to be because recovery is unique for everyone.